Deadlines and Distractions - Maria Saez-Marti; Anna Sjögren (The Research Institute of Industrial Economics (IUI), 2004)
We analyze the effect of deadlines on timing of effort when agents are occasionaly distracted. We show that agents precautiously work early when completion of the task is uncertain, but rather likely. Agents who are rarely distracted will always postpone effort since the risk of not completing is small. As a result, increasing the probability of being distracted may even increase the likelihood of meeting the deadline. We further show that introducing the possibility of having the deadline extended may improve the total probability of completing the task without reducing the probability of completing within the originally announced deadline.
Keywords: D81; J22; M50; 330; Deadlines; Timing of Effort; Optimal Incentives; Entscheidungstheorie; Arbeitsplanung; Zeit; Prinzipal-Agent-Theorie; Theorie